Competences that foster digital transformation of public administrations: An Austrian case study - Noella Edelmann; Ines Mergel; Thomas Lampoltshammer (Administrative Sciences, 2023)
Digitalisation has changed society, and, as a result, public administrations are required to undergo significant changes to satisfy emergent societal needs. These changes impact all areas of the public sector, including the development and provision of digital services, the design of processes, and the development of policy. To implement the digital strategies and transformation requirements, public administrations must rethink the competences that their workforce as well as the external stakeholders may need. To understand how one nation implements its digital strategy and upskills its civil servants, we conducted a qualitative analysis of 41 Austrian expert interviews. The research shows that different stakeholders require a variety of competences to participate in the digital transformation of its processes and services. The results demonstrate the high level of diversity and the need for a holistic approach to tackle the complexity of the digital public sector, where leadership plays the most important role. In addition, the study shows that the use of competence frameworks for measurement and monitoring needs to be adapted to the local context.
Keywords: 350; Austria; competences; digital transformation; public administrations; qualitative research